Analisa Keperluan Latihan Terhadap Kompetensi Kepimpinan di Kalangan Pemimpin Unit-Unit (Cawangan) SABERKAS Kuching - Mohammad Nur Azhar, Mazlan (Universiti Malaysia Sarawak (UNIMAS), 2000)
Training need analysis (TNA) is the most important aspects in order to conduct an effective training programme. Effective TNA enables organisations, either profit or non-profit, to have a well developed human resource in terms of both skill and quality. This study aims to identify the relationship between demographic factors (age, level of education and experience) and leadership competency (organising, planning, decision making and communicating). The sample of this study was 33 unit's (branch) presidents of SABERKAS Association. A questionnaire was used to obtain information related to the leadership training needs. Frequencies and percentages were collected on the background of respondents, the administration of SABERKAS, types of activities and training, level of competency and the aims of SABERKAS Association. The Pearson Correlation Test was used to test the relationship between leadership competency and leadership training needs. The study found a significant relationship between leadership training need and competency of organising (r = 0.574, p = 0.000), the competency of planning (r = 0.685, p = 0.000), the competency of decision making (r = 0.459), p = 0.007) and the competency of communicating (r = 0.814, p = 0.000). Therefore, it is recommended that the unit's (branch) presidents of SABERKAS Association to be trained in those competency in order to strengthen the skill of leadership in the future.